Compact FSS Absorber Design Using Resistively Loaded Quadruple Hexagonal Loops For Bandwidth Enhancement - Cahill, Robert; Zabri@Suhaimi, Siti Normi; Schuchinsky, Alexander G. (Institution of Engineering and Technology, 2015)
The design of a thin microwave absorber which exhibits a −10 dB reflectivity bandwidth of 108% at normal incidence and 16% for simultaneous suppression of TE and TM polarised waves over the angular range 0–45° is presented. The structure consists of a 3 mm-thick metal backed frequency selective surface (FSS) with four resistively loaded hexagonal loop elements in each unit cell. The surface resistivity and width of the loops are carefully chosen to maximise the bandwidth by merging the reflection nulls that are generated by the multi-resonant absorber. Measurement and simulation results are in good agreement over the broad frequency range 7.8–24 GHz. Introduction: